Farmer-herder conflicts, tenure insecurity and farmer's investment decisions in Agogo, Ghana - Selorm Kobla Kugbega; Prince Young Aboagye (Agricultural and Food Economics, 2021)
Owing to climate change, population growth and tenurial changes, the past decade has witnessed high interest among migrant and settler pastoralist groups in the vegetal-rich customary lands of the Agogo Traditional Area. This has resulted in lease grants of large land areas to pastoralists by traditional authorities and usufruct families, for reasons of ensuring optimum use and gaining the highest returns from lands. This paper examines the implications of consequent competing interests over land resources between farmers and herders on indigenous farmer's agricultural investment decisions. The study uses qualitative methods and empirical evidence is given by primary data from semi-structured interviews and focus group discussions in the case study area. Results indicated that land owners exploit lapses in customary land administration systems to allocate lands in exchange for money, to pastoralists while neglecting indigenous farmers' land use rights. Thus, indigenous farmers report land tenure insecurity and a sense of deprivation from their customary lands. Despite tenure insecurity concerns, farmer's agricultural investment decisions remain unchanged because such changes in investment decisions may reduce incomes and compromise their livelihoods. The findings herein contradict theoretical expectations and provide new perspectives for understanding the relationship between tenure (in)security and investment decisions.
Keywords: 330; Agogo; Customary land; Land tenure (in)security; Pastoralists; Usufructs